2014
DOI: 10.1016/j.trb.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the value of travel time and of travel time reliability in road networks

Abstract: This study proposes two network models which simultaneously estimate the value of travel time and of travel time reliability based on the risk-averse driver's route choice behaviour. The first model is formulated as a utility maximization problem under monotonic and separable link travel times, whereas the second model is formulated as a utility maximization problem under non-monotonic and non-separable link travel times. The proposed models have the same structure as a user equilibrium (UE) traffic assignment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 36 publications
(43 reference statements)
0
22
0
Order By: Relevance
“…Based on this hourly counting ( Table 1) the hourly social costs (based on the emissions and value of travel time and changes in travel time) of private cars [24] and tram users (based on the value of travel time and changes in travel time) can be estimated [25]. The tram users were also surveyed.…”
Section: Methodsmentioning
confidence: 99%
“…Based on this hourly counting ( Table 1) the hourly social costs (based on the emissions and value of travel time and changes in travel time) of private cars [24] and tram users (based on the value of travel time and changes in travel time) can be estimated [25]. The tram users were also surveyed.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Uchida (2014) shows that travel time variances can be approximated analytically by assuming independence between link travel times or assuming fixed exogenous correlation coefficients between link flows. However, both assumptions are unrealistic and limit the applicability.…”
Section: Methods 3: Idealmentioning
confidence: 99%
“…As shown in Clark and Watling [6], (19) and (20) can be calculated by applying a method proposed by Isserlis [35] given the moments of by assuming that the link flow follows normal distribution [17,18,33]. This assumption was supported by Rakha et al [36], which demonstrated that the normality assumption may be sufficient from a practical standpoint given its computational simplicity.…”
Section: Stochastic Link Travel Time and Stochastic Path Travelmentioning
confidence: 99%
“…Uchida et al [16] address network design problem in a stochastic multimodal network model. Uchida [17] proposed a model which simultaneously estimates the value of travel time and of travel time reliability based on the risk-averse driver's path choice behavior. Uchida [18] proposed a network equilibrium model which estimates travel time reliability from the observed link flows in the network.…”
Section: Introductionmentioning
confidence: 99%